Risperidone Attenuates Modified Stress–Re-stress Paradigm-Induced Mitochondrial Dysfunction and Apoptosis in Rats Exhibiting Post-traumatic Stress Disorder-Like Symptoms - Garabadu D.; Ahmad A.; Krishnamurthy S. (My University, 2025)
Mitochondria play a significant role in the pathophysiology of post-traumatic stress disorder (PTSD). Risperidone and paroxetine were evaluated for their effect on mitochondrial dysfunction and mitochondria-dependent apoptosis in discrete brain regions in modified stress re-stress (SRS) animal model of PTSD. Male rats were subjected to stress protocol of 2 h restraint and 20 min forced swim followed by halothane anesthesia on day 2 (D-2). Thereafter, rats were exposed to re-stress (forced swim) on D-8 and at 6-day intervals on D-14, D-20, D-26, and D-32. The rats were treated with risperidone (0.01, 0.1, and 1.0 mg/kg p.o.) and paroxetine (10.0 mg/kg p.o.) from D-8 to D-32. Risperidone at median dose and paroxetine ameliorated modified SRS-induced depressive-like symptom (increase in immobility period) in forced swim, anxiety-like behavior (decrease in percentage of open arm entries and time spent) in elevated plus maze and cognitive deficits (loss in spatial recognition memory) in Y-maze tests on D-32. Risperidone, but not paroxetine, attenuated modified SRS-induced decreases in plasma corticosterone levels. Risperidone ameliorated increase in the activity of mitochondrial respiratory complex (I, II, IV, and V), decreases in the levels of mitochondrial membrane potential, cytochrome-C and caspase-9 in the hippocampus, hypothalamus, pre-frontal cortex, and amygdala. However, both drugs attenuated modified SRS-induced increase in the number of apoptotic cells and caspase-3 levels in all the brain regions indicating anti-apoptotic activity of these drugs. Hence, these results suggest that anti-apoptotic activity could be a common mechanism for anti-PTSD-like effect irrespective of the pathways of apoptosis in the modified SRS model. © 2015, Springer Science+Business Media New York.